Legal Education and Digital Discipline in Pesantren: Fostering Santri’s Legal Awareness in the Age of Social Media - Heni Satar Nurhaida; Siti Asdiqoh (Nurul Jadid University, 2026)
The rapid expansion of digital technology and the widespread use of social media have introduced new challenges for fostering legal awareness among young people, including santri in pesantren environments. This article examines how legal education is implemented within pesantren to cultivate santri’s legal awareness related to social media use. Employing a qualitative approach with a case study design, the research was conducted. Data were collected through in-depth interviews, field findings, and document analysis, and were analyzed using thematic analysis. The findings reveal that pesantren apply internal regulations that are firm yet educational in nature, including restrictions on mobile phone ownership and use, direct supervision by administrators and kyai, and the application of educational sanctions. These regulatory practices function not merely as administrative rules, but as instruments for internalizing discipline, responsibility, and legal awareness in digital contexts. Nevertheless, the study also identifies persistent challenges, particularly the inconsistency between pesantren regulations and formal school policies, as well as santri’s strong curiosity toward social media trends. To address these challenges, pesantren adopt adaptive strategies such as inter-institutional coordination, guided supervision, and the habituation of disciplined behavior. Overall, the study highlights the strategic role of pesantren in integrating digital legal education with Islamic values and Islamic educational management in responding to contemporary digital realities.